Design and optimization of a probiotic tablet for gastrointestinal tolerance by a simplex-centroid mixture. - Mohd Akmal, Azhar; Mimi Sakinah, Abdul Munaim (Taylor & Francis, 2020)
In this study, a simplex-centroid mixture design using design of experiment (DOE) software was implemented to evaluate the effect of biopolymers as excipients, which are hydroxypropyl methylcellulose, and alginate, on the gastrointestinal tolerance of probiotic tablet containing Saccharomyces boulardii. Microbial viability and dissolution time were used to evaluate the ideal formulation made using 39.01% carboxymethylcellulose and 60.99% alginate as excipients, which protected the probiotics from the acidic condition in the stomach with good dissolution time. The formulated probiotic tablet is more stable in terms of viability when stored at 4 C compared to room temperature. However, the viability remains above 106 CFU/tablet after six months of storage at room temperature. This study shows that the simplex-centroid mixture design is valid and can be used to formulate probiotic tablets that possess gastrointestinal tolerance. This study can lead to the development of commercial production of probiotic yeast tablets with gastrointestinal tolerance.